(untitled) (Research, Society and Development, 2022)
Discussion of the benefits of rotary files is essential in endodontic treatment because patient comfort and safety during the performance of a procedure is fundamental. Through proper treatment and the correct use of dental tools, the patient’s health is complemented, relieving pain during procedures. This study aims to analyze the main benefits of using rotary files for endodontic treatment. Also, check the function of the rotary files and the proper handling by the dental surgeon. This is an integrative literature review in which the delimited consultation platforms are: SciELO, LILACS and Institutional Repositories. For this, the following search descriptors were used: Rotating Files; Endodontic treatment; Dental surgeon. The application of some criteria was limited: temporality - articles published in 2014-2022; methodological – literary, integrative, systematic reviews and field research. In this way, the benefits of using rotary files are presented in the literature and demonstrate resistance to the material of the patient’s tooth, thus preventing these instruments from breaking during the procedure, requiring the surgeon to have previous skills to handle the files to avoid intercurrences. Therefore, a well-performed procedure enables successful treatment of the patient.